Assessing the Predictability of WRF Model for Heavy Rain by Cold Air Associated with the Easterly Wind at High-Level Patterns over Mid-Central Vietnam - Tien Toan, Nguyen; Thanh, Cong; Thi Phuong, Pham; Tuan Anh, Vu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1S, 2018)
Abstract: In this study, we assessed the predictibility of precipitation due to cold air associated with the easterly wind at the high level using WRF model with 2 days lead time for the Mid-Central Vietnam region. The results show that the 24-hour forecasts lead time should use medium rainfall threshold (16-50 mm/day) and heavy rain (50-100 mm/day) for quantitative precipitation forecast and rainfall area reference; the 48-hour forecast lead time should choose moderate rainfall threshold. For threshold above 100 mm, the results of all forecast lead time are not good and almost unpredictable. The results of this study may help gain more information for forecasting rainfall due to cold air associated easterly wind at the high level for the Mid-Central Vietnam region. Keywords : WRF model, heavy rainfall over mid-central Vietnam. References: [1] Chang, C.-P., Yi, L., Chen, G.T.-J.,(2000), A numerical simulation of vortex development during the 1992 east Asian summer monsoon onset using the navy's regional model. Mon. Weather Rev. 128, 1604–1631 [2] Yasunari, T., Miwa, T., (2006), Convective cloud systems over the Tibetan plateau and their impact on meso-scale disturbance in the Meiyu/Baiu frontal zone—a case study in 1998. J. Meteorol. Soc. Jpn. 84, 783–803. [3] Bùi Minh Tăng, 2014, Báo cáo tổng kết đề tài “Nghiên cứu xây dựng công nghệ dự báo mưa lớn thời hạn 2-3 ngày phục vụ công tác cảnh báo sớm lũ lụt khu vực miền trung Việt Nam”, Đề tài độc lập cấp nhà nước. [4] Ulrich Damrath (2002). “Verification of the operational NWP models at DWD“.